Isolation and evaluation of probiotic potential of lactic acid bacteria in village chicken gastrointestinal tract. - Lingoh, Arlene Debbie (2020)
Currently, small-scale poultry industries are still utilising feed-additive antibiotics in livestock growth improvement and feed efficiency although it has been banned due to the increased incidences of antibiotic resistance among zoonotic bacteria and the loss of therapeutic efficacy in both veterinary and human medicine. A group of lactic acid bacteria in probiotic, which is a live beneficial microbial feed supplement has been used in commercial animal feed as substitution to the antibiotic. However, the continuous increase in demand for organic farming in food-producing animals clearly necessitate probiotic strains with more effective properties to reduce diseases and improve productivity. This study was conducted purposely to identify and characterize potential probiotic properties and diversity of lactic acid bacteria isolated from the intestinal tract of village chicken. Village chickens that have not been fed any commercial feed have been used as a source of potential probiotic strains to prevent a source of antibioticresistant lactic acid bacteria. Five village chickens were caught randomly from every four locations around Bintulu to collect the crop, gizzard, small intestine, large intestine and cecum. Samples were processed and plated for bacterial colony count. 800 bacteria were isolated, clustered and analysed using (GTG)5 fingerprinting and probiotic analysis test. Phenotypic characterization resulted in only 21 isolates possess the lactic acid bacteria characteristics such as gram-positive, catalase-negative, non-motile and able to ferment glucose. Genotypic characterization has identified that the isolated lactic acid bacteria was Enterococcus, Lactobacillus and Bacillus. Only isolates CR1AM6, L1M10, C4M8, L4AM2 and L4AM5 has shown resistant towards bile salt, pepsin and acidic condition which will enable these strains to survive the harsh condition in the gut. These isolates also able to ferment inulin which is beneficial towards the host as it helps the live microbiota to be implemented easily in the gut.